2020
DOI: 10.1093/jnci/djaa105
|View full text |Cite|
|
Sign up to set email alerts
|

p16/ki67 and E6/E7 mRNA Accuracy and Prognostic Value in Triaging HPV DNA-Positive Women

Abstract: Background The study presents cross-sectional accuracy of E6/E7 mRNA detection and p16/ki67 dual staining, alone or in combination with cytology and HPV16/18 genotyping, as triage test in HPV DNA-positive women and their impact on CIN2+ overdiagnosis. Methods Women aged 25-64 were recruited. HPV DNA-positives were triaged with cytology and tested for E6/E7 mRNA and p16/ki67. Cytology positives were referred to colposcopy, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 31 publications
7
45
0
2
Order By: Relevance
“…Our study results are essentially consistent with the data from other reports on the evaluation of the diagnostic performance of p16/Ki67 dual-stained cytology for triaging HPV-positive cases [15,20,21,24]. All comparator studies involved groups of women <30 years, and most of them included women aged 21-24, as was designed in our investigation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study results are essentially consistent with the data from other reports on the evaluation of the diagnostic performance of p16/Ki67 dual-stained cytology for triaging HPV-positive cases [15,20,21,24]. All comparator studies involved groups of women <30 years, and most of them included women aged 21-24, as was designed in our investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Similarities with several studies in the sensitivity levels for detection HSIL (CIN2+) obtained in our screening model 1 were noted, including the study of the New Technologies for Cervical Cancer Screening group [24] (81.8%), the report of the Wentzensen et al [20] (86.8%) in a comparable to our size study and the ATHENA sub-study trial-similarities with our results were observed only in the group with p16/Ki67 triaging N16/N18 HPVpositive test results (82.8%) [15]. A difference was found with the ATHENA study in the specificity for HSIL (CIN2+) detection (75.6% reported in the ATHENA).…”
Section: Discussionsupporting
confidence: 87%
“…In a recent meta-analysis, its sensitivity and specificity to detect cervical intraepithelial neoplasia of grade 2 (CIN2 + ), 3 or worse (CIN3 + ) ranged from 82–86% and 49–71%, respectively [ 41 ]. When combined with Ki67 IHC, p16 showed a sensitivity of 75.2% to detected CIN2 + , compared to 61.0% achieved by cytology alone [ 42 ]. In HNSCC, p16 IHC sensitivity to detect HPV-positive cases is high (92%, 95% CI 82–97%), while its specificity seems to be moderate (72%, 95% CI 45–89%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tests for E6/E7 oncoproteins present a promising option for triaging screen-positive women given high positive predictive value and limited laboratory equipment ( 145 ). However, more than 60% of HPV positive women were also E6/E7 mRNA positive ( 146 ), which would present a challenge in identifying women with precancerous lesions. A systematic review of three types of HPV E6/E7 mRNA tests (Aptima, Quantivirus, and PreTect Proofer) found that while the tests have diagnostic relevance to detect CIN2-3, the higher specificity of some tests is due to the limited number of HPV types it detects ( 147 ).…”
Section: Resultsmentioning
confidence: 99%